2023
DOI: 10.3389/fenvs.2023.1051295
|View full text |Cite
|
Sign up to set email alerts
|

Assessing spatial and temporal changes in diversity of copepod crustaceans: a key step for biodiversity conservation in groundwater-fed springs

Abstract: Despite the close attention springs have received from a hydrologic perspective and as biodiversity hotspots, the multiple dimensions of spring meiofaunal assemblage diversity are still poorly investigated. Knowledge of beta diversity patterns and drivers can inform and improve management decisions on biodiversity conservation. Here, we analyzed beta diversity of copepod assemblages in karst springs in Central Italy by focusing on: 1) relative contributions of turnover and nestedness components to taxonomic an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 87 publications
0
3
0
Order By: Relevance
“…Further, we demonstrated that copepod assemblages populating a set of caves along a latitudinal gradient spanning the Italian peninsula were noticeably dissimilar from one another, with turnover rather than nestedness driving most of the observed beta diversity. This is also important from a conservation perspective because the high species turnover implies that environmental degradation within a single cave may lead to the loss of unique species not occurring elsewhere, similarly to what has emerged from a recent study performed on groundwater-fed karst springs 41 . Additionally, we showed that geographical distance had a not negligible yet secondary role in shaping the between-cave dissimilarity of copepod assemblages in our studied caves, with surface temperature patterns having the greatest influence, particularly on species replacement.…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…Further, we demonstrated that copepod assemblages populating a set of caves along a latitudinal gradient spanning the Italian peninsula were noticeably dissimilar from one another, with turnover rather than nestedness driving most of the observed beta diversity. This is also important from a conservation perspective because the high species turnover implies that environmental degradation within a single cave may lead to the loss of unique species not occurring elsewhere, similarly to what has emerged from a recent study performed on groundwater-fed karst springs 41 . Additionally, we showed that geographical distance had a not negligible yet secondary role in shaping the between-cave dissimilarity of copepod assemblages in our studied caves, with surface temperature patterns having the greatest influence, particularly on species replacement.…”
Section: Discussionmentioning
confidence: 94%
“…Nevertheless, only a few studies 33 , 36 have thus far evaluated the relative role of geographic distance and environmental gradients on biotic dissimilarity (i.e., beta diversity) of groundwater crustacean assemblages, explicitly partitioning between spatial turnover and nestedness-resultant dissimilarity 37 . Partitioning beta diversity into these two components and exploring its geographic, historical, and environmental correlates has proven to be crucial for understanding biogeographic processes 36 , 38 , 39 and outlining conservation priorities 40 , 41 .…”
Section: Introductionmentioning
confidence: 99%
“…Natural spring areas, as the unique zones where groundwater and surface water converge, boast abundant water resources and distinct ecological environments [1,2]. Research on environmental microbial communities and their functions holds significant implications worldwide [3]. In recent years, it has been discovered that microbes in groundwater environments play vital roles in maintaining aquatic ecological stability, protecting water resources, and safeguarding ecosystem health [4][5][6].…”
Section: Introductionmentioning
confidence: 99%